Severe Persistent Eczema in a Recipient of the Gam-COVID-Vac vaccine - Maryam Ameri; Meysam Abolmaali; Sayed Mohammed Jawad Alwedaie; Mohammad Nabavi; Neda Rahimian; Negin Mahmoodi (European Journal of Case Reports in Internal Medicine, 2022)
Since the beginning of the COVID-19 pandemic, efforts have been made to design safe and effective vaccines against SARS-CoV-2. Numerous vaccines have been designed and tested in limited clinical trials in various countries. Among them, the Sputnik V vaccine has shown a relatively safe profile and, to our knowledge, has no associated major side effects. We describe the case of a 40-year-old female healthcare worker who developed severe persistent eczematous lesions on the second day after she received the first dose of the Sputnik vaccine. The eczematous lesions were refractory to an antihistamine and persisted at the 1 month follow-up. Severe persistent eczematous lesions should be viewed as a potential side effect of vaccination with the Sputnik V vaccine. Moreover, a severe allergic reaction to a COVID-2019 vaccine may indicate the vaccine is ineffective in the recipient.